2012
DOI: 10.1016/j.jcf.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evidence that V456A is a Cystic Fibrosis causing mutation in South Asians

Abstract: We provide evidence that V456A can cause significant pulmonary disease in South Asian Cystic Fibrosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…ystic fibrosis (CF) is a fatal inherited disease that is common among the Caucasian population and affects 30,000 and 3,000 newborns/year in the United States and Canada, respectively (1,2). Cystic fibrosis is a multiorgan disease affecting the liver, pancreas, gastrointestinal tract, and lungs; however, pulmonary injury is the main cause of death among CF patients (3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ystic fibrosis (CF) is a fatal inherited disease that is common among the Caucasian population and affects 30,000 and 3,000 newborns/year in the United States and Canada, respectively (1,2). Cystic fibrosis is a multiorgan disease affecting the liver, pancreas, gastrointestinal tract, and lungs; however, pulmonary injury is the main cause of death among CF patients (3)(4)(5).…”
mentioning
confidence: 99%
“…The CFTR molecule is a 1,480-amino-acid membrane-bound chloride channel (7). The structure and function of the channel in CF are compromised by over 1,800 types of mutations (2). The most prevalent mutation, delta F 508, is a deletion of phenylalanine at position 508 and is responsible for 70% of CF cases worldwide (6,7).…”
mentioning
confidence: 99%
“…V456A is a missense mutation in exon 9 of CFTR which results in change of valine to an alanine in CRTR protein. Case 9 of present study and two other previously reported female cases from India and Pakistan who were homozygous for this mutation had intermediate sweat chloride concentrations with mild to moderate phenotype leading to delayed diagnosis of CF [36]. 1161delC mutation has been previously reported from Indian, Pakistani and Bahraini patients.…”
Section: Discussionmentioning
confidence: 52%
“…Data suggest that more than 160 CFTR variants have been identified on approximately 3700 Asian CF chromosomes. Overall, F508del (p.Phe508del, c.1521_1523delCTT) remains the most common variant in Asian countries with few exceptions (Table ) . However, F508del constitutes only 12–31% of Asian CF alleles compared with 66% in the worldwide CF population comprised mainly from North America, Europe, Canada, Australia and New Zealand (http://www.genet.sickkids.on.ca/app).…”
Section: Distribution and Functional Consequences Of Cftr Variants Inmentioning
confidence: 99%
“…There are 116 additional rare CFTR variants reported from Asian countries and the majority of these variants have been observed only once. Among these variants 24 are from South Asia, 54 from Middle East Asia and 38 from East Asia (Table ) . The Delexon 16‐17b variant ( CFTR dele18‐20) has been observed in both Chinese and Japanese CF individuals .…”
Section: Distribution and Functional Consequences Of Cftr Variants Inmentioning
confidence: 99%